Pelaksanaan Total Quality Management Perpustakaan Universitas Medan Area (UMA) - Pulungan, Abdullah; Sumanti, Solihah Titin; Jamil, Khairul (Darul Yasin Al Sys, 2023)
The aim of this research is to find out how Total Quality Management works in planning, organizing, actualizing, and controlling in the Medan Area University Library. The Problem Formulation of this research is How is Total Quality Management in Planning, Organizing, Actualing and Controlling in Medan Area University Libraries? This type of research uses qualitative methods with a descriptive approach. The theory used in this research is the librarian interpersonal communication theory. Data collection techniques are carried out through interviews and documentation. The results of the research show that: The implementation of Total Quality Management in the Medan Area University Library carried out by researchers at the Medan Area University (UMA) means that librarians or library employees have sufficient knowledge to answer questions about the services available in the library. Therefore, library employees often participate in library training so that they have a broader insight into libraries. So students can rely on library staff if something unexpected happens and can find solutions to the problem, so students have no difficulty getting the information they need.